Study on flow distribution pattern and conductivity of porous media in bioretention cells. Issue 2 (20th December 2021) - Wang, Yajun; Si, Yunmei; Yang, Sheng; Singh, Rajendra Prasad
ABSTRACT: To evaluate the long-term performance of bioretention cell (BRC), a study was undertaken to assess the flow distribution and conductivity. Despite initial conductivity of the original medium being the common predictor of hydraulic performance, most of the BRCs are affected by conductivity variations during actual operation. This happen due to the fact that microbial behavior plays an important role in the conductivity variations. This linkage may occur when bacteria as inert colloids transports between particles and biodegrades dissolved pollutants, either promoting or retarding flow distribution and conductivity in BRC. Flow distribution was determined by numerical simulation and tracer test, and the correlation between conductivity and flow distribution was revealed by conductivity experiment coupled with flow distribution analysis. Results revealed a non-uniform flow distribution in BRC, and seepage flow in submerged zone was virtually impossible push flow. Conductivity had an inversely proportional relationship with hydraulic efficiency where hydraulic efficiency reached the highest value (0.297) under a low hydraulic conductivity (0.000107 m/s, approximately K / K ini = 0.79). Primary cause of hydraulic capacity reduction was the initial permeability decrease due to medium structure changes. Results revealed a sharp upward trend followed by a slight decrease, and then, stabilized to a stable infiltration stage. Permeation process of sewage influent was similar to the one of potable water where the permeability reduced to 0.000102 m/s after 450 h and declined continuously. Thus, it is clear that flow distribution and conductivity in bioretention must be estimated more accurately on a microscopic scale.